Assessing IoT challenges in supply chain: A comparative study before and during- COVID-19 using interval valued neutrosophic analytical hierarchy process - KILIÇ, HÜSEYİN SELÇUK (My University, 2022)
Although the Internet of Things (IoT) has spawned a new breed of smart factories within supply chains, the latest pandemic has ushered in unparalleled supply chain disturbances. Following the challenges identified in the literature, we interview top experts to evaluate the significance of these challenges. We apply a multi criteria decision analysis (MCDA) tool, analytical hierarchy process (AHP) in combination with interval-valued neutrosophic numbers (IVN). The critical part of this research is that we also perform a comparative analysis by focusing on before-and during-the pandemic periods individually to better assess the impact of the latest pandemic on the IoT challenges. Our study also includes a comprehensive, systematic literature review to bring the readers up-to-date.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Social Sciences and Humanities; Management; İŞLETME; Ekonomi ve İş; Sosyal Bilimler (SOC); BUSINESS; ECONOMICS & BUSINESS; Social Sciences (SOC); Strateji ve Yönetim; Genel İşletme, Yönetim ve Muhasebe; İşletme ve Uluslararası Yönetim; Pazarlama; Sosyal Bilimler ve Beşeri Bilimler; Strategy and Management; General Business, Management and Accounting; Business and International Management; Marketing; Social Sciences & Humanities; Internet of Things; IoT; Industrial internet of things; IIoT; Industry 4; 0; i4; Supply chain management; COVID-19; Analytical hierarchy process (AHP); Multi-criteria decision analysis (MCDA); Interval-valued neutrosophic sets; THINGS IOT; INDUSTRY 4.0; INTERNET; SYSTEM; IMPACT; INFORMATION; MANAGEMENT; LOGISTICS; FRAMEWORK; PROSPECTS; Internet of Things; IoT; Industrial internet of things; IIoT; Industry 4.0; i4.0; Supply chain management; COVID-19; Analytical hierarchy process (AHP); Multi-criteria decision analysis (MCDA); Interval-valued neutrosophic sets